Identification Of Gray Mold On Gerbera jamesonii Plants - Shaker, G. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Obviously, within the years 2004, 2005, 2006, several infection cases of damping – off ,leaves ,flowers ,buds and petioles blight ,stem canker ,crown rot have seen on (Gerbera jamesonii) plants in nurseries and appears dirty white(brown) color mold at the first and then convert to gray color on the foliage. The studying is carried out in two locations in Baghdad city which are Palestine Street (Al-Khirat, Al-Zina nurseries) and Zaiyuna (Zainab, Zaiyuna, Baghdad nurseries). The isolation and diagnosis were identified the causal pathogen was Botrytis cinerea.The pathogenicity test was carried out with positive results were positive resulted. The infections percentage on gerbera plants ranged in the studied nurseries between (40-70%), there were no significant differences in severity rates between nurseries.